Pengaruh Kualitas Pelayanan dan Citra Perusahaan Terhadap Kepuasan Pelanggan serta Implikasinya Terhadap Loyalitas Pelanggan PT. Bank Syariah Mandiri Cabang Thamrin Jakarta - Agustina Massora; Indah Widyanti (Jurnal Manajemen FE-UB, 2021)
This study aims to determine the extent of the influence of service quality, corporate imageon customer loyalty through customer satisfaction at PT. Bank Syariah Mandiri Branch ThamrinJakarta.The data used in this study are primary data collected from respondents' answers based onthe questionnaire given, as many as 94 people. The data processing method uses the path analysismethod with the help of SPSS version 21.0. Statistical testing used individual parametersignificance test (t test) and simultaneous significance test (F test).The results showed that simultaneously the variables of service quality, company image andcustomer satisfaction have a significant effect on customer loyalty. Partially it shows that analysis1: service quality variables have a significant effect on customer loyalty, while analysis 2:company image variables have a significant effect on customer loyalty and in analysis 3:customer satisfaction variables have a significant effect on customer loyalty performance.Keywords: Service Quality, Company Image, Customer Satisfaction and Customer Loyalty1